EKSISTENSI PERAN KEPALA MADRASAH MENUJU SEKOLAH BERMUTU - Moh Sholihuddin (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Educational institutions as a forum that operates under the auspices of the government in order to carry out the vision and mission towards the success of educating the superior seeds of the future. This study uses a literature study method that relies on bibliographic sources from books and articles in scientific journals related to the subject matter. The results of this study indicate that: 1) The role of madrasah principals towards quality schools includes as leaders, educators, managers, administrators, supervisors, motivators and innovators. 2) The madrasa principal's strategy towards quality successful schools includes: a) Always analyzing student learning outcomes, exams, by examining the differences between learning outcomes and goals, b) Involving teachers in identifying needs, c) Analyzing whether programs that have been organized are still efficient for solving problems.Leadership, Principal, Mutu